Germany finds GOd. (Economist, 2019)
The article reports on the cybercrime in Germany, wherein an amateur hacker, known as G0d, leaked the phone numbers, addresses and, in some cases, private photos and credit-card details of nearly 1,000 German politicians, celebrities and journalists.